2013
DOI: 10.1186/1757-2215-6-52
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Follicle stimulating hormone modulates ovarian stem cells through alternately spliced receptor variant FSH-R3

Abstract: BackgroundWe have earlier reported that follicle stimulating hormone (FSH) modulates ovarian stem cells which include pluripotent, very small embryonic-like stem cells (VSELs) and their immediate descendants ‘progenitors’ termed ovarian germ stem cells (OGSCs), lodged in adult mammalian ovarian surface epithelium (OSE). FSH may exert pleiotropic actions through its alternatively spliced receptor isoforms. Four isoforms of FSH receptors (FSHR) are reported in literature of which FSH-R1 and FSH-R3 have biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 68 publications
10
116
0
Order By: Relevance
“…Variable expression levels (highest in OSE and contralateral ovaries with and without OETs; lowest in antral follicles, SBTs, and peritoneal implants associated with SBTs, increasing parallel to proliferation activity of OETs and decreasing level with advancing carcinoma grade) were observed Stewart et al (2004) Both gonadotropins and hormones increased OSE proliferation in rats Tan & Fleming (2004) Performed PCNA staining in normal mouse OSE and found PCNA-positive cells at sites distant from the site of follicle rupture Burdette et al (2006) Both PMSG and hCG increased OSE proliferation that could occur before and also after ovulation. No signs of apoptosis were evident in OSE post-ovulation in CD1 mice Bhartiya et al (2012) PMSG treatment results in increased FSHR expression in adult mouse OSE Patel et al (2013) FSHR expressed on the stem cells and germ cell nests in sheep OSE smears and the surrounding epithelial cells are negative…”
Section: Fsh and Fshr Isoformsmentioning
confidence: 99%
See 3 more Smart Citations
“…Variable expression levels (highest in OSE and contralateral ovaries with and without OETs; lowest in antral follicles, SBTs, and peritoneal implants associated with SBTs, increasing parallel to proliferation activity of OETs and decreasing level with advancing carcinoma grade) were observed Stewart et al (2004) Both gonadotropins and hormones increased OSE proliferation in rats Tan & Fleming (2004) Performed PCNA staining in normal mouse OSE and found PCNA-positive cells at sites distant from the site of follicle rupture Burdette et al (2006) Both PMSG and hCG increased OSE proliferation that could occur before and also after ovulation. No signs of apoptosis were evident in OSE post-ovulation in CD1 mice Bhartiya et al (2012) PMSG treatment results in increased FSHR expression in adult mouse OSE Patel et al (2013) FSHR expressed on the stem cells and germ cell nests in sheep OSE smears and the surrounding epithelial cells are negative…”
Section: Fsh and Fshr Isoformsmentioning
confidence: 99%
“…Targeted disruption of FSHR in FORKO mice resulted in abnormal gametogenesis and hormonal imbalance (Dierich et al 1998). As shown in Table 4, two studies clearly showed that FSH/pregnant mare serum gonadotropin (PMSG) treatment results in selective upregulation of Fshr3 compared with Fshr1 in mouse granulosa cells (Babu et al 2001) and in sheep OSE cells (Patel et al 2013). Sullivan et al (2013) studied FSHR transcripts by qPCR in sheep follicles segregated based on the size into small, medium, and large.…”
Section: R37mentioning
confidence: 99%
See 2 more Smart Citations
“…The somatic stem cells in the OSE have been investigated in three distinct contexts: potential stem cells able to regenerate germ cells (Parte et al 2011, Patel et al 2013, Virant-Klun et al 2013a, potential stem cells that give rise to granulosa cells (Hummitzsch et al 2013), and more traditional somatic stem cells whose role is to replenish the OSE following ovulatory wounding (Szotek et al 2008, Motohara et al 2011, Usongo & Farookhi 2012, Auersperg 2013, Flesken-Nikitin et al 2013, Ng et al 2014. While this review focuses briefly on studies that have addressed somatic stem cells that are thought to be required for ovulatory wound repair, the relationship with the HGSEOC of the two former potential stem cell pools cannot be discounted.…”
Section: Somatic Stem Cells Of the Osementioning
confidence: 99%